2013
DOI: 10.1002/jsfa.6205
|View full text |Cite
|
Sign up to set email alerts
|

Digestive recovery of sulfur‐methyl‐l‐methionine and its bioaccessibility in Kimchi cabbages using a simulated in vitro digestion model system

Abstract: Results from our study suggest that SMM from Kimchi cabbages, a component of food sources, is more bioavailable than SMM by itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The method used in this study was designed by Lee et al 9 The in vitro digestion model system, including the human gastrointestinal tract, including salivary, gastric, and small intestinal phases, was simulated as described previously 5 . Approximately 5 mg of GTC and 5 mg of HPMCP-coated GTCs were suspended in 5-mL aliquots of 20 mM phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The method used in this study was designed by Lee et al 9 The in vitro digestion model system, including the human gastrointestinal tract, including salivary, gastric, and small intestinal phases, was simulated as described previously 5 . Approximately 5 mg of GTC and 5 mg of HPMCP-coated GTCs were suspended in 5-mL aliquots of 20 mM phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The bioaccessibility of rutin from blended juice containing various fruits to increase vitamin C was found to be 22.16%, which was 1.12 and 1.16 times lower than that of SGV and SGK, respectively [38]. A previous study demonstrated that the bioaccessibility of vit U digested from Kimchi cabbage was higher than that of vit U alone [33]. In a similar finding, the study reported that 8.83%, 14.71%, and 10.88% of bioaccessibility were found for salivary, gastric, and small intestinal parts.…”
Section: Resultsmentioning
confidence: 99%
“…We investigated whether vit U can act as a natural excipient ingredient to promote bioaccessibility and digestive absorption of SGV. The fact that matrix significantly influences the bioavailability or bioactivity of vit U has been demonstrated in the in vitro digestion model system [31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…It implies that oral intake of 3.98 kg of celery per day will be needed. Previous study found that SMM was unstable under digestive fluid with 0.68% of digestive recovery during in vitro digestion, suggesting that a high dosage of SMM is necessary to show specific biological activites by oral intake (Lee and others ). To our knowledge, there was limited study on the absorption of SMM.…”
Section: Introductionmentioning
confidence: 99%